Penerapan V-Model Untuk Merancang Sistem Aplikasi Penerimaan Peserta Didik Baru Studi Kasus SDN 056639 Jasa Makmur - Rianto; Romulo P. Aritonang (Institut Teknologi dan Bisnis Indonesia, 2025)
Several stages of the new student admission process are also carried out by SDN 056639 Jasa Makmur. SDN 056639 Jasa Makmur. is an institution engaged in the field of education consisting of an elementary school located at Jl. Jasa Makmur, Harapan Jaya Village, Sei Lepan District, Langkat Regency, North Sumatra 20857. This school has 17 teachers and 6 classes with an average of 30 to 50 students each. Based on the problems that occur above, a New Student Admissions Application System Design (PPDB) system is needed which will later be developed with the V-Model method, which can help schools manage PPDB and help prospective students in the PPDB process, especially at SDN 056639 Jasa Makmur, both registration and information on the results of the PPDB announcement online. With this system, participants and parents of participants do not need to bother coming to school just to see announcements or information related to the implementation of PPDB. Whenever and wherever they are, they can do it via a computer or smartphone connected to the internet.